Mekanisme Molekuler Imunomodulasi oleh Huangqi (Astragali Radix) Menggunakan Sistem Farmakologi Jejaring - Raymond Rubianto Tjandrawinata; Anindini Winda Amalia; Hartati Tuna; Viedya Novalinda Said; Santi Tan (Fakultas Farmasi Universitas Pancasila, 2022)
Astragali Radix (Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao, also known as Huangqi) has been used to improve stamina and immunity for thousands of years. However, the bioactive components and their mechanisms are still unclear, limiting its clinical application. In this research, for the first time, network pharmacology was used to investigate the molecular mechanisms of Huangqi and its bioactive components that play an important role in improving the immune system. An amount of 1,430 immunomodulation-related target proteins was collected from the human genome database, with 171 target proteins from 20 bioactive components, and resulted in 60 intersection target proteins. Subsequently, the networks of common target and protein-protein interaction (PPI) were analyzed. The results showed that Huangqi influenced the modulations of lymphocytes (B cells and T cells), natural killer cells, macrophages, cytokines, immunoglobulins, and immune signal transduction. To a certain limit, this study revealed the potential bioactive components and pharmacological mechanisms of Huangqi in immunomodulation. It was able to direct novel drug development for treating immune system deficiency.